Pengaruh Return on Asset (ROA) dan Return on Equity (ROE) terhadap Harga Saham pada Perusahaan Pertambangan Batu Bara yang Terdaftar di Bursa Efek Indonesia - Nadya Rosada; A. Rozi; Evrina (ARZUSIN, 2026)
Although the relationship between profitability and stock prices has been widely investigated, previous studies have yielded inconsistent results, particularly among coal mining companies during periods of economic change and commodity price fluctuations. This study aimed to analyze the effects of Return on Assets (ROA) and Return on Equity (ROE), both partially and simultaneously, on the stock prices of coal mining companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employed a quantitative approach with an explanatory associative design. The sample consisted of five companies selected using purposive sampling, resulting in 25 firm-year observations. Data were collected through the documentation of financial statements and stock price information from the Indonesia Stock Exchange, Yahoo Finance, and Stockbit, and were subsequently analyzed using multiple linear regression with IBM SPSS 26. The results showed that ROA had a negative and significant effect on stock prices (β = −1.843; p = 0.021), whereas ROE had no significant effect on stock prices (β = 0.571; p = 0.182). Simultaneously, ROA and ROE had no significant effect on stock prices (p = 0.054), with a coefficient of determination of 23.3%. These findings indicate that profitability indicators have not fully explained movements in the stock prices of coal mining companies. This study emphasizes that stock price valuation needs to consider profitability alongside market conditions, commodity price dynamics, and corporate risk. Future studies need to expand the sample coverage, apply panel data analysis, and incorporate other financial and macroeconomic variables.